2020
DOI: 10.3390/app10249044
|View full text |Cite
|
Sign up to set email alerts
|

Model of Complex Heat Transfer in the Package of Rectangular Steel Sections

Abstract: During heat treatment of rectangular steel sections, a heated charge in the form of regularly arranged packages is placed in a furnace. The article presents a model of a complex heat transfer in such a package using the thermo-electric analogy. The model considers the following types of heat transfer: conduction in section walls, conduction and natural convection within gas, heat radiation between the walls of a section, as well as contact conduction between the adjacent sections. The results of our own experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…It was also demonstrated that above 300 • C, thermal radiation is essential for the whole phenomenon. In the next article [41,42], the complex heat transfer in the packages of rectangular steel sections was analyzed in turn. It was established that the heat transfer intensity in such systems mostly depends on the thermal contact resistance R ct between adjacent layers of the package.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also demonstrated that above 300 • C, thermal radiation is essential for the whole phenomenon. In the next article [41,42], the complex heat transfer in the packages of rectangular steel sections was analyzed in turn. It was established that the heat transfer intensity in such systems mostly depends on the thermal contact resistance R ct between adjacent layers of the package.…”
Section: Resultsmentioning
confidence: 99%
“…At a temperature of 675 • C, this value ranges from 0.09 to 0.25. The increase in Kr with temperature can be explained by the effect of thermal radiation that takes place in the area of the porous charge between the surfaces of individual components (bars or sections) [42,48].…”
mentioning
confidence: 99%
“…In order to prepare the samples, bars from low-carbon steel with the carbon content of 0.2% were used. The change in the thermal conductivity of such steel in the temperature function (where temperature is expressed in • C) is described by the following relationship [36]: The results of the measurement of effective thermal conductivity are presented in the form of diagrams. Figure 4a presents the results obtained for samples made of 5 × 20 mm bars, whereas Figure 4b shows the results for samples made of 10 × 40 mm bars.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, the concept of an elementary cell has been used. It is a commonly used approach in which the effective thermal conductivity is calculated based on the analysis of thermal resistances (the so-called electrical analogy) [ 19 , 20 , 21 , 22 , 23 ]. The coefficient k ef for a defined elementary cell has been calculated from the Equation (18) where: l cell —characteristic dimension of the elementary cell, R cell —total thermal resistance of the cell.…”
Section: Methodsmentioning
confidence: 99%
“…Values of the coefficients A1-A3 from Equation(21) and characteristic dimension of the elementary cell lcell obtained for particular samples.…”
mentioning
confidence: 99%